3D high-resolution two-photon crosslinked hydrogel structures for biological studies. (June 2017) - Brigo, Laura; Urciuolo, Anna; Giulitti, Stefano; Della Giustina, Gioia; Tromayer, Maximilian; Liska, Robert; Elvassore, Nicola; Brusatin, Giovanna
Graphical abstract: Abstract: Hydrogels are widely used as matrices for cell growth due to the their tuneable chemical and physical properties, which mimic the extracellular matrix of natural tissue. The microfabrication of hydrogels into arbitrarily complex 3D structures is becoming essential for numerous biological applications, and in particular for investigating the correlation between cell shape and cell function in a 3D environment. Micrometric and sub-micrometric resolution hydrogel scaffolds are required to deeply investigate molecular mechanisms behind cell-matrix interaction and downstream cellular processes. We report the design and development of high resolution 3D gelatin hydrogel woodpile structures by two-photon crosslinking. Hydrated structures of lateral linewidth down to 0.5 µm, lateral and axial resolution down to a few µm are demonstrated. According to the processing parameters, different degrees of polymerization are obtained, resulting in hydrated scaffolds of variable swelling and deformation. The 3D hydrogels are biocompatible and promote cell adhesion and migration. Interestingly, according to the polymerization degree, 3D hydrogel woodpile structures show variable extent of cell adhesion and invasion. Human BJ cell lines show capability of deforming 3D micrometric resolved hydrogel structures. Statement of Significance: The design and development of high resolution 3D gelatin hydrogel woodpile structures by two-photon crosslinking is reported. Significantly, topological and mechanical conditions of polymerized gelatin structures were suitable for cell accommodation in the volume of the woodpiles, leading to a cell density per unit area comparable to the bare substrate. The fabricated structures, presenting micrometric features of high resolution, are actively deformed by cells, both in terms of cell invasion within rods and of cell attachment in-between contiguous woodpiles. Possible biological targets for this 3D approach are customized 3D tissue models, or studies of cell adhesion, deformation and migration.